2022
DOI: 10.1055/s-0042-1757628
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Spinal Robotic Systems and Pedicle Screw Accuracy Rates: Review of Literature and Meta-Analysis

Abstract: Introduction The motivation to improve accuracy and reduce complication rates in spinal surgery has driven great advancements in robotic surgical systems, with the primary difference between the newer generation and older generation models being the presence of an optical camera and multijointed arm. This study compares accuracy and complication rates of pedicle screw placement in older versus newer generation robotic systems reported in the literature. Methods We performed a systemic review and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…While the use of robotics systems has been described for the treatment of adult spinal deformity, the vast majority of these have been for open surgery or descriptions of S2-alar-iliac screw placement [24]. MIS placement of screws in short-segment degenerative pathologies has also been well reported [15,27,28], but their use for long-segment complex deformity correction has been described less frequently. Our series herein thereby serves to illustrate that long-segment constructs can be designed for MIS correction of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of robotics systems has been described for the treatment of adult spinal deformity, the vast majority of these have been for open surgery or descriptions of S2-alar-iliac screw placement [24]. MIS placement of screws in short-segment degenerative pathologies has also been well reported [15,27,28], but their use for long-segment complex deformity correction has been described less frequently. Our series herein thereby serves to illustrate that long-segment constructs can be designed for MIS correction of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al performed a meta-analysis that shows that robot-assisted system interventions achieved an 88.9% grade A according to the GR classification, compared to 84.0% for freehand screw placement [23]. Additionally, the learning curve for robotassisted PSP is reported to be significantly shorter than that of the manual technique [24].…”
Section: Robot-assisted Drillingmentioning
confidence: 99%
“…According to a systematic review in 2017, the accuracy of the early models (SpineAssist, Renaissance, ROSA robot) ranged from 85% to 100% [ 2 ]. Moreover, a meta-analysis reported in 2022 showed that the accuracy of the older generation models (SpineAssist, Renaissance) was 97%, while the newer generation models (Mazor X, Excelsius GPS, ROSA Spine, TINAVI) exhibited an accuracy of 99%, indicating that the newer models were more precise [ 3 ].…”
Section: Introductionmentioning
confidence: 99%